Determining factors of child linear growth from the viewpoint of Bronfenbrenner's Bioecological Theory - Gabriela Rossiter Stux Veiga; Gisélia Alves Pontes da Silva; Bruna Merten Padilha; Marilia de Carvalho Lima (Elsevier, 2023)
Objective: To analyze the factors associated with children's linear growth, according to the different subsystems of the 6Cs model and Bronfenbrenner's Bioecological Theory. Data sources: Narrative review, carried out in the Scielo, Lilacs, Pubmed, and Science Direct databases, based on research using the terms Bioecological Theory, child growth, and risk factors, combined with the use of Boolean operators. Summary of findings: According to the 6Cs model, proposed based on Bronfenbrenner's Bioecological Theory, the determining factors of children's linear growth are in six interrelated subsystems - cell, child, clan, community, country/state and culture. The empirical studies included in this review made it possible to analyze protection and risk factors within the subsystems. Among the protective factors: are adequate birth weight and satisfactory weight gain, breastfeeding for six months or more; proper hygienic habit of hand washing, proper elimination of feces, and access to clean water. As risk factors: low, birth weight and size, prematurity, multiple deliveries, short interval between deliveries, non-exclusive breastfeeding until the 3rd month, frequency and severity of infectious processes and anemia, little parental education, short maternal statur, inadequate maternal nutritional status, domestic violence, family poverty, food, and nutritional insecurity, living in rural areas or at high altitudes. Conclusion: Children's linear growth is determined by interrelated factors that encompass aspects prior to the child's birth, as well as socioeconomic, political, family and community issues.